2016
DOI: 10.12785/jtte/040106
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Knowledge and Syntactic Awareness as Potential Catalysts for Reading Comprehension among Young Jordanian EFL Students

Abstract: This study examines the potential effect of vocabulary knowledge and syntactic awareness on Jordanian ninth grade students' reading comprehension. The data were collected using pre-/post-reading comprehension, vocabulary, and grammar tests and an interview. The findings reveal significant differences (at α ≤ 0.05) in the students' reading comprehension scores on the posttest in favor of the experimental group. A number of implications and recommendations for future research are put forth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Furthermore, Jordanian researchers (e.g., Al-Jamal, Hawamleh, & Al-Jamal, 2013; [6] Al-Damiree & Bataineh, 2015; [2] Smadi&AlShra'ah, 2015; [31] Bataineh & Mayyas, 2017; [15] Al-Khamaiseh & Al-Jamal, 2022) [7] indicated that EFL Jordanian students face problems while reading, as contributed to the lack of proper instructional strategy. To overcome this problem, integrating self-questioning strategy may improve students' reading comprehension skills.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Furthermore, Jordanian researchers (e.g., Al-Jamal, Hawamleh, & Al-Jamal, 2013; [6] Al-Damiree & Bataineh, 2015; [2] Smadi&AlShra'ah, 2015; [31] Bataineh & Mayyas, 2017; [15] Al-Khamaiseh & Al-Jamal, 2022) [7] indicated that EFL Jordanian students face problems while reading, as contributed to the lack of proper instructional strategy. To overcome this problem, integrating self-questioning strategy may improve students' reading comprehension skills.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Reading is a complex skill that entails different variables, and having proficient readers is important at all stages both in Jordan and around the globe (Al-Damiree & Bataineh, 2016). Some of the major topics to be discussed are reading literacy, reader characteristics, instructional design, extensive reading, literary instruction in EFL reading, and reading assessment (Hedgcock & Ferris, 2009).…”
Section: Research Bodymentioning
confidence: 99%
“…Despite the many endeavors to improve the quality of EFL instruction in general and reading instruction in particular, EFL students at all levels are reported to suffer from difficulties in reading and reading comprehension (Al-Makhzoumi, 1986;Bataineh & Al-Barakat, 2005, 2011Bataineh & Al-Shorman, 2005, Bataineh & Alqatanani, 2011AlKhawaldeh, 2012;Smadi & Alshra'ah, 2015;Al-Damiree & Bataineh, 2016, Bataineh & Al-Kofeiri, 2018. Although many researchers examined reading difficulties for EFL students (Bataineh & Barakat, 2005;Hussien, 2012;Al-Jamal, Hawamleh, & Al-Jamal, 2013;Qrqez & Ab Rashid, 2017), further research is needed to identify the potential obstacles that face EFL reading.…”
Section: Problem Of the Studymentioning
confidence: 99%